Edge coating binder for lithium ion battery, preparation method of edge coating binder and edge coating slurry
By using polyacrylic resin and hot melt resin emulsion to blend the edge-coated adhesive in lithium-ion batteries, the safety hazards caused by separator shrinkage of lithium-ion batteries are solved, and the effect of improving battery safety and performance is achieved.
Patent Information
- Application Number
- CN202411422344.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-03-28
AI Technical Summary
The temperature of the lithium-ion battery rises during operation, causing the diaphragm to shrink, which in turn causes a short circuit in contact with the positive and negative electrodes, which poses a safety hazard.
A polyacrylic resin is prepared by a two-step process by mixing a polyacrylic resin with a hot melt resin emulsion to form a new type of water-based edge-coated adhesive. This adhesive has good thermal stability and adhesive properties, and can effectively prevent the diaphragm from shrinking.
The safety and performance of lithium-ion batteries are significantly improved, and the thermal stability of the diaphragm is improved, and the risk of shrinkage caused by rising temperature is reduced, thereby avoiding the occurrence of contact short circuits of positive and negative electrodes.
Smart Images

Figure CN119709061A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium ion batteries, and in particular to an edge coating adhesive for lithium ion batteries and a preparation method thereof, and an edge coating slurry. Background Art
[0002] As the core energy source of modern portable electronic devices and electric vehicles, the performance of lithium-ion batteries directly affects the efficiency and endurance of the equipment. In the construction of lithium-ion batteries, the traditional winding process is convenient and efficient, but due to the curvature of the winding corners, the space utilization rate is relatively low. Therefore, the use of the stacking process can make more full use of the battery space, thereby significantly improving the energy density under the same volume of battery cell design. However, the temperature of the battery gradually rises during operation, and the diaphragm shrinks after being heated, which leads to a short circuit between the positive and negative electrodes, posing a safety hazard.
[0003] In order to solve this problem, negative electrode side coating technology has gradually attracted attention in recent years and has become one of the key technologies for improving battery performance. The conventional practice in the prior art is to use PAA as a binder for negative electrode side coating, but the bonding effect of using PAA alone is poor. Based on this, the present invention proposes a new side coating binder for lithium-ion batteries, a preparation method thereof, and a side coating slurry containing the side coating binder. Summary of the invention
[0004] Based on the above description, the present invention provides a side-coating adhesive for lithium-ion batteries and its preparation method, and a side-coating slurry to solve the problem in the prior art that the temperature of the battery gradually rises during operation, the diaphragm shrinks after being heated, and then causes a short circuit between the positive and negative electrodes.
[0005] The technical solution of the present invention to solve the above technical problems is as follows:
[0006] In a first aspect, the present invention provides an edge coating adhesive for lithium ion batteries, which is a solution formed by blending a polyacrylic resin and a hot-melt resin emulsion;
[0007] The polyacrylic acid resin is a low Tg multipolymer, and the raw materials of the polyacrylic acid resin include a hydrophilic soft monomer, a hydrophobic soft monomer, a hydrophilic monomer and a functional monomer, with a mass ratio of 25 to 35:10 to 30:10 to 25:30 to 45;
[0008] The hydrophilic soft monomer, the hydrophobic soft monomer, the hydrophilic monomer and the functional monomer all contain carbon-carbon double bonds and contain one or more groups selected from amide groups, hydroxyl groups, carboxyl groups, cyano groups and ester groups.
[0009] Based on the above technical solution, the present invention can also be improved as follows.
[0010] Furthermore, the hydrophilic soft monomer is hydroxyethyl acrylate, hydroxyethyl methacrylate and methoxy polyethylene glycol monoacrylate, and the mass ratio is 5-15:5-10:20-35.
[0011] Furthermore, the hydrophobic soft monomer is an acrylic ester monomer.
[0012] Furthermore, the hydrophobic soft monomer is isooctyl acrylate, n-butyl acrylate and ethyl acrylate, and the mass ratio is 5-10:10-20:10-25.
[0013] Furthermore, the hydrophilic monomer is acrylonitrile.
[0014] Furthermore, the functional monomers include acrylic acid, methacrylic acid and acrylamide in a mass ratio of 10-15:5-10:15-35.
[0015] Furthermore, the hot-melt resin emulsion includes one or more of ethylene-acrylic acid copolymer, ethylene-vinyl acetate copolymer and ethylene-butene copolymer.
[0016] In a second aspect, the present invention provides a method for preparing an edge coating adhesive for a lithium ion battery as described in the first aspect, comprising the following steps:
[0017] S1. Add deionized water, functional monomers, hydrophilic soft monomers, and chain transfer agent into a polymerization kettle equipped with a thermometer and a stirring paddle; pass nitrogen to deoxygenate, add hydrophilic monomers and hydrophobic soft monomers, stir evenly, add initiator dropwise for the first time, and react at 60-70°C for 3h;
[0018] S2, adding the initiator dropwise for the second time, mixing the functional monomer and the hydrophilic soft monomer with deionized water evenly and adding dropwise, reacting at 60-70° C. for another 3 h, and neutralizing the solution with sodium carbonate to a pH of 7 after the reaction to obtain a polyacrylic acid resin;
[0019] S3, uniformly mixing the polyacrylic acid resin obtained in step S2 and the hot-melt resin emulsion according to a preset ratio to obtain a side coating adhesive for lithium-ion batteries.
[0020] In a third aspect, the present invention provides an edge coating slurry obtained by mixing the edge coating binder for lithium ion batteries as described in the first aspect with sodium carboxymethyl cellulose, boehmite and water.
[0021] Compared with the prior art, the technical solution of this application has the following beneficial technical effects:
[0022] The invention provides an edge coating adhesive for lithium ion batteries and a preparation method thereof. The edge coating adhesive for lithium ion batteries comprises a solution formed by blending a polyacrylic acid resin and a hot-melt resin emulsion; wherein the polyacrylic acid polymer is a low-Tg multi-polymer, and the raw materials of the polyacrylic acid resin comprise a hydrophilic soft monomer, a hydrophobic soft monomer, a hydrophilic monomer and a functional monomer, with a mass ratio of 25 to 35:10 to 30:10 to 25:30 to 45; the hydrophilic soft monomer, the hydrophobic soft monomer, the hydrophilic monomer and the functional monomer all contain a carbon-carbon double bond, and contain one or more groups of an amide group, a hydroxyl group and a carboxyl group.
[0023] Compared with existing methods, this scheme has the following advantages:
[0024] The edge coating adhesive provided by the present invention is a water-based PAA edge coating adhesive, which is a mixture of a linear polymer and a nanoparticle resin, has a low viscosity, and has good processing performance. It is applied to lithium-ion batteries, has good thermal stability, bonds copper foil and diaphragms, prevents diaphragm shrinkage, and can effectively improve the safety of lithium-ion batteries.
[0025] Furthermore, the edge-coating adhesive and edge-coating slurry provided by the present invention combine polyacrylic acid resin with hot-melt resin emulsion for the first time, obtain polyacrylic acid resin by two-step method, and then form a new type of water-based edge-coating adhesive. The blending of polyacrylic acid resin and hot-melt resin emulsion can not only give full play to the advantages of both, but also maintain good bonding performance under high temperature environment; the flexibility and heat resistance of the edge-coating slurry can effectively improve the thermal stability of the diaphragm after pulping with materials such as boehmite, reduce the risk of shrinkage caused by temperature increase, and thus significantly improve the safety and performance of the battery.
[0026] In summary, the edge-coating adhesive and edge-coating slurry provided by the present invention have excellent thermal stability, and the preparation method is simple, the cost is low, and it is easy to prepare on a large scale. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a graph showing the test results of the differential scanning calorimetry (DSC) of the edge coating adhesive for lithium ion batteries provided in Example 1 of the present invention;
[0028] Figure 2 Schematic diagram of the preparation process of the edge coating slurry provided in Example 1 of the present invention. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the drawings of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] The following is combined with Figure 1 and Figure 2 The embodiments of the present invention are further described in detail with examples. The following examples are used to illustrate the present invention but cannot be used to limit the scope of the present invention.
[0031] The invention provides an edge coating adhesive for lithium ion batteries, which is a solution formed by blending polyacrylic acid resin and hot-melt resin emulsion.
[0032] Among them, the polyacrylic acid resin is a low Tg multipolymer, and the raw materials of the polyacrylic acid resin include hydrophilic soft monomers, hydrophobic soft monomers, hydrophilic monomers and functional monomers, with a mass ratio of 25-35:10-30:10-25:30-45;
[0033] The hydrophilic soft monomer, the hydrophobic soft monomer, the hydrophilic monomer and the functional monomer all contain a carbon-carbon double bond and contain one or more of an amide group, a hydroxyl group, a carboxyl group, a cyano group and an ester group.
[0034] Preferably, the hydrophilic soft monomer is an acrylate monomer containing a hydrophilic group.
[0035] Specifically, the hydrophilic soft monomer may be hydroxyethyl acrylate, hydroxyethyl methacrylate and methoxy polyethylene glycol monoacrylate, with a mass ratio of 5-15:5-10:20-35.
[0036] Preferably, the hydrophobic soft monomer is an acrylate monomer.
[0037] Specifically, the hydrophobic soft monomer is isooctyl acrylate, n-butyl acrylate and ethyl acrylate, and the mass ratio is 5-10:10-20:10-25.
[0038] Preferably, the hydrophilic monomer is acrylonitrile.
[0039] Preferably, the functional monomers include acrylic acid, methacrylic acid and acrylamide in a mass ratio of 10-15:5-10:15-35.
[0040] Preferably, the hot-melt resin emulsion includes one or more of ethylene-acrylic acid copolymer, ethylene-vinyl acetate copolymer and ethylene-butene copolymer.
[0041] The preparation method of the edge coating adhesive comprises the following steps:
[0042] S1. Add deionized water, functional monomers, hydrophilic soft monomers, and chain transfer agent into a polymerization kettle equipped with a thermometer and a stirring paddle; pass nitrogen to deoxygenate, add hydrophilic monomers and hydrophobic soft monomers, stir evenly, add initiator dropwise for the first time, and react at 60-70°C for 3h;
[0043] S2, adding the initiator dropwise for the second time, mixing the functional monomer and the hydrophilic soft monomer with deionized water evenly and adding dropwise, reacting at 60-70° C. for another 3 h, and neutralizing the solution with sodium carbonate to a pH of 7 after the reaction to obtain a polyacrylic acid resin;
[0044] S3, uniformly mixing the polyacrylic acid resin obtained in step S2 and the hot-melt resin emulsion according to a preset ratio to obtain a side coating adhesive for lithium-ion batteries.
[0045] Correspondingly, the edge coating slurry is obtained by mixing the edge coating binder as mentioned above with sodium carboxymethyl cellulose, boehmite and water.
[0046] The technical solution of this patent is further described in detail below in conjunction with specific embodiments.
[0047] Example 1
[0048] This embodiment provides a method for preparing an edge coating binder for lithium ion batteries, which adopts a two-step method to prepare a polyacrylic acid resin, comprising the following steps:
[0049] Step S1, in a polymerization kettle equipped with a thermometer and a stirring paddle, add deionized water, 5.3% by mass of acrylic acid (AA), 1.3% by mass of methacrylic acid (MAA), 26.67% by mass of acrylamide (AM), 20% by mass of hydroxyethyl acrylate (HEA), hydroxyethyl methacrylate (HEMA) and methoxypolyethylene glycol monoacrylate (MPGA) mixed solution, 1.0% by mass of isopropyl alcohol (IPA), wherein isopropyl alcohol (IPA) is used as a chain transfer agent; nitrogen is passed through to deoxygenate (water oxygen content <0.1ppm); 6.7% by mass of acrylonitrile (AN) and 6.7% by mass of a mixed solution of isooctyl acrylate (2-EHA), n-butyl acrylate (BA) and ethyl acrylate (EA) are added, stirred evenly, and an initiator ammonium persulfate (APS) with a monomer concentration of 1.0% is added dropwise, and the reaction is carried out at 70°C for 3h.
[0050] Step S2, dropwise add initiator APS with a monomer concentration of 0.5%, mix 2.7% AA, 0.7% MAA, 13.33% AM, 10% HEA, HEMA, MPGA, 0.5% IPA, 3.3% AN and 3.3% 2-EHA, BA, EA by mass fraction, evenly add, react at 70° C. for 3 hours, and after the reaction, neutralize the solution with sodium carbonate to pH 7 to obtain a polyacrylic acid resin.
[0051] Step S3, mixing the polyacrylic acid resin and the hot-melt resin emulsion, ethylene-acrylic acid copolymer (EAA), in a ratio of 5:5 to obtain a water-based edge coating adhesive for lithium-ion batteries.
[0052] Furthermore, boehmite and sodium carboxymethyl cellulose (CMC) were uniformly mixed at a ratio of 100:0.5, and then mixed with a water-based edge-coating binder at a ratio of 1:1, and the solid content was adjusted to 42% to obtain a water-based edge-coating binder slurry.
[0053] like Figure 2 As shown, the preparation route in this embodiment is to first use a two-step method to prepare a polyacrylic resin, then mix the polyacrylic resin with a hot-melt resin emulsion to obtain an aqueous edge-coating adhesive; and blend the aqueous edge-coating adhesive boehmite with sodium carboxymethyl cellulose (CMC) to obtain an edge-coating slurry.
[0054] The obtained water-based edge coating adhesive was subjected to a peeling test, and the test method was as follows:
[0055] (1) Apply the edge coating slurry onto the copper foil using a 200m scraper and dry it;
[0056] (2) Using 7 MPa pressure and 100°C hot pressing for 1 min, the diaphragm-bonded electrode is obtained.
[0057] The PAA viscosity, edge coating adhesive viscosity, pH, stability, edge coating slurry viscosity, pole piece peel strength, etc. were tested. The test results are shown in Table 1.
[0058] also, Figure 1 The figure shows the differential scanning calorimetry (DSC) test results of the edge-coated adhesive for lithium-ion batteries provided in this embodiment, and the results show that the edge-coated adhesive has a lower glass transition temperature.
[0059] Example 2
[0060] This embodiment provides a method for preparing an edge coating binder for lithium ion batteries, which adopts a two-step method to prepare a polyacrylic acid resin, comprising the following steps:
[0061] Steps S1 and S2 are the same as S1 and S2 in the above-mentioned embodiment 1.
[0062] Step S4, mixing the polyacrylic acid resin and the hot-melt resin emulsion, ethylene-vinyl acetate copolymer (EVA), in a ratio of 5:5 to obtain a water-based edge coating adhesive for lithium-ion batteries.
[0063] Furthermore, the method for obtaining the water-based edge-coating adhesive slurry is the same as that in the above-mentioned embodiment 1, which will not be repeated here, to obtain the water-based edge-coating adhesive slurry.
[0064] The obtained water-based edge coating adhesive was subjected to a peeling test, and the test method was the same as that of the above-mentioned Example 1, which will not be repeated here. The test results are shown in Table 1.
[0065] Example 3
[0066] This embodiment provides a method for preparing an edge coating binder for lithium ion batteries, which adopts a two-step method to prepare a polyacrylic acid resin, comprising the following steps:
[0067] Steps S1 and S2 are the same as S1 and S2 in the above-mentioned embodiment 1.
[0068] Step S3, mixing the polyacrylic resin and the hot-melt resin emulsion, polyolefin copolymer (POE), in a ratio of 5:5 to obtain a water-based edge coating adhesive for lithium-ion batteries.
[0069] Furthermore, the method for obtaining the water-based edge-coating adhesive slurry is the same as that in the above-mentioned embodiment 1, which will not be repeated here, to obtain the water-based edge-coating adhesive slurry.
[0070] The obtained water-based edge coating adhesive was subjected to a peeling test, and the test method was the same as that of the above-mentioned Example 1, which will not be repeated here. The test results are shown in Table 1.
[0071] Example 4
[0072] This embodiment provides a method for preparing an edge coating binder for lithium ion batteries, which adopts a two-step method to prepare a polyacrylic acid resin, comprising the following steps:
[0073] Steps S1 and S2 are the same as S1 and S2 in the above-mentioned embodiment 1.
[0074] Step S3, mixing the polyacrylic acid resin and the hot-melt resin emulsion, ethylene-acrylic acid copolymer (EAA) and ethylene-vinyl acetate copolymer (EVA) in a ratio of 5:2:3 to obtain a water-based edge coating adhesive for lithium-ion batteries.
[0075] Furthermore, the method for obtaining the water-based edge-coating adhesive slurry is the same as that in the above-mentioned embodiment 1, which will not be repeated here, to obtain the water-based edge-coating adhesive slurry.
[0076] The obtained water-based edge coating adhesive was subjected to a peeling test, and the test method was the same as that of the above-mentioned Example 1, which will not be repeated here. The test results are shown in Table 1.
[0077] Example 5
[0078] This embodiment provides a method for preparing an edge coating binder for lithium ion batteries, which adopts a two-step method to prepare a polyacrylic acid resin, comprising the following steps:
[0079] Steps S1 and S2 are the same as S1 and S2 in the above-mentioned embodiment 1.
[0080] Step S3, mixing the polyacrylic acid resin and the hot-melt resin emulsion, ethylene-vinyl acetate copolymer (EVA), in a ratio of 7:3 to obtain a water-based edge coating adhesive for lithium-ion batteries.
[0081] Furthermore, the method for obtaining the water-based edge-coating adhesive slurry is the same as that in the above-mentioned embodiment 1, which will not be repeated here, to obtain the water-based edge-coating adhesive slurry.
[0082] The obtained water-based edge coating adhesive was subjected to a peeling test, and the test method was the same as that of the above-mentioned Example 1, which will not be repeated here. The test results are shown in Table 1.
[0083] Example 6
[0084] This embodiment provides a method for preparing an edge coating binder for lithium ion batteries, which adopts a two-step method to prepare a polyacrylic acid resin, comprising the following steps:
[0085] Steps S1 and S2 are the same as S1 and S2 in the above-mentioned embodiment 1.
[0086] Step S3, mixing the polyacrylic acid resin and the hot-melt resin emulsion, ethylene-vinyl acetate copolymer (EVA), in a ratio of 3:7 to obtain a water-based edge coating adhesive for lithium-ion batteries.
[0087] Furthermore, the method for obtaining the water-based edge-coating adhesive slurry is the same as that in the above-mentioned embodiment 1, which will not be repeated here, to obtain the water-based edge-coating adhesive slurry.
[0088] The obtained water-based edge coating adhesive was subjected to a peeling test, and the test method was the same as that of the above-mentioned Example 1, which will not be repeated here. The test results are shown in Table 1.
[0089] Comparative Example 1
[0090] This comparative example provides a method for preparing an edge coating adhesive, which adopts a one-pot method to prepare a polyacrylic acid resin, comprising the following steps:
[0091] Step S1, in a polymerization kettle equipped with a thermometer and a stirring paddle, add deionized water, 8% by mass of acrylic acid (AA), 42% by mass of acrylamide (AM), 30% by mass of hydroxyethyl acrylate (HEA), hydroxyethyl methacrylate (HEMA) and methoxy polyethylene glycol monoacrylate (MPGA) mixed solution, pass nitrogen gas to deoxygenate (water oxygen content <0.1ppm), add 10% by mass of acrylonitrile (AN) and 10% by mass of isooctyl acrylate (2-EHA), n-butyl acrylate (BA), ethyl acrylate (EA) mixed solution, stir evenly, dropwise add initiator ammonium persulfate (APS) with a monomer concentration of 1.5%, and react at 60°C for 3h. After the reaction, use sodium carbonate to neutralize the solution to a pH of 7 to obtain a polyacrylic acid resin.
[0092] Step S2, mixing the polyacrylic acid resin and the hot-melt resin emulsion, ethylene-acrylic acid copolymer (EAA), in a ratio of 5:5 to obtain an edge coating adhesive.
[0093] Furthermore, boehmite and sodium carboxymethyl cellulose (CMC) were uniformly mixed at a ratio of 100:0.5, and then mixed with the edge coating binder at a ratio of 1:1, and the solid content was adjusted to 42% to obtain edge coating binder slurry.
[0094] The obtained edge coating adhesive was subjected to a peeling test, and the test method was as follows:
[0095] (1) Apply the edge coating slurry onto the copper foil using a 200m scraper and dry it;
[0096] (2) Using 7 MPa pressure and 100°C hot pressing for 1 min, the diaphragm-bonded electrode is obtained.
[0097] The PAA viscosity, edge coating adhesive viscosity, pH, stability, edge coating slurry viscosity, pole piece peel strength, etc. were tested. The test results are shown in Table 1.
[0098] Comparative Example 2
[0099] This comparative example provides a method for preparing an edge coating adhesive, which adopts a one-pot method to prepare a polyacrylic acid resin, comprising the following steps:
[0100] Step S1, in a polymerization kettle equipped with a thermometer and a stirring paddle, deionized water, 8% mass fraction acrylic acid (AA), 2% mass fraction methacrylic acid (MAA), 40% mass fraction acrylamide (AM), 30% mass fraction hydroxyethyl acrylate (HEA), hydroxyethyl methacrylate (HEMA) and methoxy polyethylene glycol monoacrylate (MPGA) mixed solution, 1.5% mass fraction isopropyl alcohol (IPA), wherein isopropyl alcohol (IPA) is used as a chain transfer agent, nitrogen is passed through to deoxidize (water oxygen content <0.1ppm), 10% mass fraction acrylonitrile (AN) and 10% mass fraction of isooctyl acrylate (2-EHA), n-butyl acrylate (BA), ethyl acrylate (EA) mixed solution are added, stirred evenly, and an initiator ammonium persulfate (APS) with a monomer concentration of 1.5% is added dropwise, and the reaction is carried out at 60°C for 3h. After the reaction is completed, the solution is neutralized to a pH of 7 using sodium carbonate to obtain a polyacrylic acid resin.
[0101] Step S2 is the same as the above comparative example 1 and will not be described again here, to obtain the edge coating adhesive.
[0102] Furthermore, the method for obtaining the edge-coating adhesive slurry is the same as that of the above-mentioned comparative example 1, which will not be described again here, to obtain the water-based edge-coating adhesive slurry.
[0103] The obtained water-based edge coating adhesive was subjected to a peeling test, and the test method was the same as that of the above comparative example 1, which will not be repeated here. The test results are shown in Table 1.
[0104] Comparative Example 3
[0105] On the basis of Example 1, step S4 is included, and only pure PAA is used as a binder. The preparation and testing methods of the binder slurry are the same as those in the example.
[0106] Comparative Example 4
[0107] Pure EVA emulsion was used as the binder. The binder slurry preparation and testing methods were the same as those in the example.
[0108] Table 1
[0109]
[0110] From the test results in Table 1, we can see that:
[0111] (1) By comparing Examples 1 to 6 with Comparative Example 3, it can be found that the edge coating slurry using PAA alone has good stability and processability, but poor bonding effect; By comparing Examples 1 to 6 with Comparative Example 4, EVA is used alone. Since EVA itself has a low viscosity, the viscosity is too low after being configured into edge coating slurry. The slurry has too good fluidity during processing, the coated electrode is thin, and the bonding force is poor.
[0112] (2) The adhesive of Comparative Example 1 has the highest viscosity, and the stability after mixing PAA and EAA is average, and the peel strength is low. This is because the one-pot polymerization is used for the partial polymerization of PAA, and the viscosity is high, which affects the viscosity of the subsequent composite adhesive, and then affects the processing performance of the edge coating slurry. It is impossible to prepare a suitable electrode, indicating that the one-pot method has disadvantages;
[0113] Compared with Example 1, Comparative Example 2 adds chain transfer agents IPA and MAA, and compared with Comparative Example 1 and Comparative Example 2, Example 1 changes the one-pot polymerization into a two-step polymerization. The viscosity of Comparative Example 2 is reduced, and the viscosity of Example 1 is greatly reduced compared with Comparative Example 1. Therefore, the addition of chain transfer agent and MAA, and the two-step polymerization are beneficial to improving the processing performance. The peel strength of Example 1 reaches 22N / m.
[0114] (3) Compared with Comparative Examples 1 and 2 and Example 1, in Example 2 and Example 3, the hot-melt resin emulsion EAA is replaced with EVA and POE, and the stability of the composite adhesive is improved and the peel strength is enhanced.
[0115] (4) Example 4 adopts the method of mixing EAA and EVA emulsion to prepare the edge coating slurry, and the peel strength is stable; Compared with Example 4, Example 5 increases the proportion of PAA and reduces the proportion of EVA, and the viscosity difference is not large, but the peel strength decreases slightly; Compared with Example 4, Example 6 reduces the proportion of PAA and increases the proportion of EVA, the viscosity of the glue and slurry decreases, and the peel strength does not change much.
[0116] Compared with conventional edge coating adhesives, the present invention adopts the method of blending polyacrylic acid resin (PAA) solution and hot-melt resin emulsion to obtain a composite adhesive. On the one hand, polyacrylic acid resin (PAA) can coordinate or complex with Cu due to its strong polar groups such as carboxyl and nitrile groups, so as to achieve the effect of bonding copper foil; at the same time, due to the addition of low Tg monomers during polymerization, the polymer has a certain flexibility. After mixing with the hot-melt resin, during hot pressing, the PAA molecular chain and the resin molecular chain will slip and entangle with the holes of the diaphragm to achieve the effect of bonding the diaphragm. The preparation method is simple, carried out at room temperature and pressure, with low energy consumption, high yield, low cost, and easy to promote and prepare on a large scale.
[0117] In summary, compared with the prior art, the present embodiment can achieve the following technical effects: the edge-coating adhesive and edge-coating slurry provided by the present invention combine polyacrylic acid resin with hot-melt resin emulsion for the first time, and adopt a two-step method to form a new type of polyacrylic acid resin, and then generate an edge-coating adhesive. The blending of polyacrylic acid resin and hot-melt resin emulsion can not only give full play to the advantages of both, but also maintain good bonding properties under high temperature environment; the flexibility and heat resistance of the hot-melt resin emulsion make it possible to effectively improve the thermal stability of the diaphragm after slurrying with substances such as boehmite, reduce the risk of shrinkage caused by increased temperature, thereby significantly improving the safety and performance of the battery.
[0118] In the description of this specification, the description with reference to the terms "specific example" or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the embodiment of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example.
[0119] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A side coating adhesive for lithium ion batteries, characterized in that: It is a solution formed by blending polyacrylic resin and hot-melt resin emulsion; The polyacrylic acid resin is a low Tg multipolymer, and the raw materials of the polyacrylic acid resin include a hydrophilic soft monomer, a hydrophobic soft monomer, a hydrophilic monomer and a functional monomer, with a mass ratio of 25 to 35:10 to 30:10 to 25:30 to 45; The hydrophilic soft monomer, the hydrophobic soft monomer, the hydrophilic monomer and the functional monomer all contain carbon-carbon double bonds and contain one or more groups selected from amide groups, hydroxyl groups, carboxyl groups, cyano groups and ester groups.
2. The edge coating adhesive for lithium ion batteries according to claim 1, characterized in that: The hydrophilic soft monomer is an acrylic ester monomer containing a hydrophilic group.
3. The edge coating adhesive for lithium ion batteries according to claim 2, characterized in that: The hydrophilic soft monomers are hydroxyethyl acrylate, hydroxyethyl methacrylate and methoxy polyethylene glycol monoacrylate, and the mass ratio is 5-15:5-10:20-35.
4. The edge coating adhesive for lithium ion batteries according to claim 1, characterized in that: The hydrophobic soft monomer is an acrylic ester monomer.
5. The edge coating adhesive for lithium ion batteries according to claim 4, characterized in that: The hydrophobic soft monomers are isooctyl acrylate, n-butyl acrylate and ethyl acrylate, and the mass ratio is 5-10:10-20:10-25.
6. The edge coating adhesive for lithium ion batteries according to claim 1, characterized in that: The hydrophilic monomer is acrylonitrile.
7. The edge coating adhesive for lithium ion batteries according to claim 1, characterized in that: The functional monomers include acrylic acid, methacrylic acid and acrylamide, and the mass ratio is 10-15:5-10:15-35.
8. The edge coating adhesive for lithium ion batteries according to claim 1, characterized in that: The hot-melt resin emulsion includes one or more of ethylene-acrylic acid copolymer, ethylene-vinyl acetate copolymer and ethylene-butene copolymer.
9. A method for preparing an edge coating adhesive for lithium ion batteries according to any one of claims 1 to 8, characterized in that: The steps include: S1. Add deionized water, functional monomers, hydrophilic soft monomers, and chain transfer agent into a polymerization kettle equipped with a thermometer and a stirring paddle; pass nitrogen to deoxygenate, add hydrophilic monomers and hydrophobic soft monomers, stir evenly, add initiator dropwise for the first time, and react at 60-70°C for 3h; S2, adding the initiator dropwise for the second time, mixing the functional monomer and the hydrophilic soft monomer with deionized water evenly and adding dropwise, reacting at 60-70° C. for another 3 h, and neutralizing the solution with sodium carbonate to a pH of 7 after the reaction to obtain a polyacrylic acid resin; S3, uniformly mixing the polyacrylic acid resin obtained in step S2 and the hot-melt resin emulsion according to a preset ratio to obtain a side coating adhesive for lithium-ion batteries.
10. An edge coating slurry, characterized in that: The adhesive is obtained by mixing the edge coating adhesive for lithium ion batteries as claimed in any one of claims 1 to 8 with sodium carboxymethyl cellulose, boehmite and water.
Citation Information
Cited By
Polymer microsphere for battery coating diaphragm as well as preparation method and application of polymer microsphere
CN120248225A